Elementos estruturais de um jogo digital: camadas de informação, mídia, processos e criação de mecânicas - Silva, Alexandre Vieira da (2023)
The research seeks to discuss the structures that make up the digital game, considering its multidisciplinarity. The thesis is based on the works of Jesse Schell and Katie Salen and Erick Zimmerman to discuss a structure that organizes the layers of information in a digital game, in order to make them more accessible to design activity and teaching of digital games. Based on this proposal, the work suggests organizing the informational structure of the digital game by categorizing it into 3 layers: Semantic, Technological and Interactive. Where, the Semantic layer groups all language areas; Technological guides discussions on programming logic and technological supports; and the Interactive layer deals with systems relevant to digital games, their nature and processes. Faced with this proposal, the thesis also discusses the nature of media within the creative process in game development, and addresses how the singularities of the support suggest different solutions from the responses delivered to linear and non-interactive media. The research deepens in the interactive layer, to propose a formal structure to the digital game that can guide, mainly, the construction of new mechanics of digital games, seeking the observation and adaptation of natural systems through its gamification process. At this point, construction models based on different starting points for the creative process are suggested. Where, the activity can start from the adoption of an already existing game genre; of a narrative; or a system